COMPLEX INTERPOLATION FOR PREDUAL SPACES OF MORREY-TYPE SPACES - Yuan, Wen (Taiwanese journal of mathematics, 2014)
In this paper, the author introduces the inhomogeneous Hausdorff type Besov and Triebel-Lizorkin spaces, which are the predual spaces of Besov-Morrey and Triebel-Lizorkin-Morrey spaces. By calculating the Calderón product of the sequence spaces related to Hausdorff type Besov and Triebel-Lizorkin spaces, the author obtains the complex interpolation of these spaces. In particular, the complex interpolation for the predual spaces of Morrey spaces is also obtained. 2010Mathematics Subject Classification: Primary 46B70; Secondary 46E35. Key words and phrases: Besov space, Triebel-Lizorkin space, Morrey spaces, Hausdorff capacity, Complex interpolation, Calderón product, Quasi-Banach lattice.